Double Spinal Dural Arteriovenous Fistulas - El-Serwi, A. (AJNR Am J Neuroradiol, 2006)
SUMMARY: We present a patient with double spinal dural arteriovenous fistulas revealed by progressive myelopathy. Numerous dilated veins extending along the entire length of the spinal cord were found on MR imaging. Angiography showed a first spinal dural fistula at the level of T7 with descending venous drainage and a second spinal dural fistula at the level of T5 with ascending venous drainage. Both fistulas were cured by therapeutic embolization.